Corporate community relations and development: engagement with indigenous peoples. Issue 4 (21st May 2021) - Blesia, Jhon Urasti; Wild, Susan; Dixon, Keith; Lord, Beverley Rae
Abstract : Purpose: The purpose of this paper is to increase knowledge about community relations and development (CRD) activities done in conjunction with mining activities of multinational companies affecting indigenous peoples and thus help improve relationships between them, despite continuing bad consequences the people continue to endure. It is through such better relationships that these consequences may be redressed and mitigated, and greater sharing of benefits of mining may occur, bearing in mind what constitutes benefits may differ from the perspectives of the indigenous peoples and the miners. Design/methodology/approach: A qualitative approach is taken, including interviews with company officials responsible for CRD activities, elaborated with observations, company and public documents and previous literature about these mining operations and the peoples. Findings: The CRD activities have gradually increased compared with their absence previously. They are officially labelled social investment in community development programmes, and are funded from profits and couched in terms of human development, human rights, preservation of culture and physical development of infrastructure. Dissatisfied with programme quality and relevance, company officials now relate with indigenous people, their leaders and representatives in ways called engagement and partnerships. Practical implications: The findings can inform policies and practices of the parties to CRD, which in this West Papua case would be the miners and their company, CRD practitioners, the indigenous peoples and the civil authorities at the local and national level and aid industry participants. Social implications: The study acknowledges and addresses social initiatives to develop the indigenous peoples affected by mining. Originality/value: The study extends older studies in the same territory before CRD had matured, and corroborates and elaborates other studies of CRD in different territories.